Investigating Lexical Progression through Lexical Diversity Metrics in a Corpus of French L3 - Paula Lissón; Nicolas Ballier (Discours)
This article presents a corpus-based evaluation of 13 lexical diversity metrics as measures of longitudinal progression in written productions of learners of French as third language (L3). Our case study (24 learners, 3 productions per learner in the course of 3 months) deals with a semi-longitudinal corpus, where each of the productions is supposed to be more complex than the previous one. Random forests (Breiman, 2001; Hothorn et al., 2019) are used in order to see whether lexical diversity metric scores capture enough vocabulary diversity progression to predict the production wave. We report that lexical diversity metrics capture lexical progression through the three productions of each student. In particular, two metrics appear to be the most informative for lexical progression: Herdan’s C and Yule’s K.